2007
DOI: 10.1002/pros.20688
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of decreased Galectin‐3 expression in the pathogenesis and progression of prostate cancer

Abstract: Drosophila telomeres comprise DNA sequences that differ dramatically from those of other eukaryotes. Telomere functions, however, are similar to those found in telomerase‐based telomeres, even though the underlying mechanisms may differ. Drosophila telomeres use arrays of retrotransposons to maintain chromosome length, while nearly all other eukaryotes rely on telomerase‐generated short repeats. Regardless of the DNA sequence, several end‐binding proteins are evolutionarily conserved. Away from the end, the Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 23 publications
5
41
1
Order By: Relevance
“…Not only the intensity of galectin-3 expression but also its intracellular distribution and extracellular concentration were found to be important for cancer progression. In human prostate cancer, galectin-3 expression was reported to be down-regulated with progressive stages (22). We demonstrated that although the levels of intact galectin-3 decreased, the levels of galectin-3 cleaved by proteases increased with progression of the prostate cancer (23).…”
mentioning
confidence: 77%
“…Not only the intensity of galectin-3 expression but also its intracellular distribution and extracellular concentration were found to be important for cancer progression. In human prostate cancer, galectin-3 expression was reported to be down-regulated with progressive stages (22). We demonstrated that although the levels of intact galectin-3 decreased, the levels of galectin-3 cleaved by proteases increased with progression of the prostate cancer (23).…”
mentioning
confidence: 77%
“…A variety of studies demonstrated a role of galectin-3 expression in tumor progression, 12,18 including hematological malignancies. 15,17,41 However, little is known about the prognostic implication of its expression in AML.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, it may promote drug resistance in chronic myeloid leukemia. 17 In contrast, decreased galectin-3 expression is associated with tumor progressions 18 and poor prognosis in other cancers, such as gastric cancer 19 and clear cell renal carcinoma. 20 To date, little is known about the clinical implication of galectin-3 expression in acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Gal-3 controls homotypic and heterotypic aggregation of prostate cancer cells (14)(15)(16) and controls their viability (17). Tumor cell expression of Gal-3 has been proposed to delineate the transition from benign stages to castration-resistant malignant disease (18) and its regulated expression is associated with promoter methylation (19). Silencing Gal-3 results in decreased migration, invasion, and proliferation of prostate cancer cells (20).…”
Section: Introductionmentioning
confidence: 99%